Review of Lorryia Oudemans, 1925 (Acari: Tydeidae: Tydeinae) associated with Hevea spp. in Brazil - Nuvoloni, Felipe M.; Mondin, Alexandre De S. [UNESP]; Feres, Reinaldo J. F. [UNESP] (Taylor & Francis, 2020)
Tydeidae are free living mites, found in a wide range of environments in all continents. Surveys of mite fauna associated with Hevea spp. have registered Lorryia mites as unidentified species, with L. formosa Cooreman, 1958 the only fully identified species. We examined 557 Lorryia specimens sampled from Hevea spp. from 26 plots distributed over 11 provinces in Brazil during the last 20 years. The analysis revealed eight species of Lorryia found on these hosts, four of them recently discovered associated with this host and three recorded for the first time in the country, besides L. formosa, which was already known on this host plant.
Keywords: Crop; mite diversity; rubber trees; species occurrence; taxonomy